Helminths of Wied’s marmoset (Callithrix kuhlii (Coimbra-Filho, 1985) (Primates: Callitrichidae)) from the Atlantic Forest, Southern Bahia State, Brazil - Soares, Aléxia David Santos; da Silva, Márcio Borba; Fraga, Ricardo Evangelista; Hoppe, Estevam Guilherme Lux [UNESP]; Oliveira, Wilson Junior [UNESP]; Schiavetti, Alexandre (FapUNIFESP (SciELO), 2024)
Callithrix kuhlii is present in forest mosaics, edge habitats, and abandoned fields in the Atlantic Forest. In Bahia and Minas Gerais. This study aimed to identify helminths from C. kuhlii and relate them to the clinical data, weights, and indices of the liver and gonads. Necropsies were performed on 13 adult marmosets that were run over on the BA-001 highway. A principal component analysis (PCA) was conducted to describe the relationships between the variables investigated. Fifty-one helminths were collected from 30.77% (4/13) of the marmosets analyzed. Helminths were classified based on their morphological and morphometric characteristics. Primasubulura jacchi (Marcel, 1857), Platynosomum illiciens (Dougherty, 1946), and Prosthenorchis confusus (Dougherty, 1946) were the species identified, with prevalence rates of 7.69%, 7.69%, and 15.38%, respectively. In addition, this is a new host record of P. confusus. The two main axes of the PCA explained a high variability (PCA=67.7%), indicating reduced weight and indices of the organs of parasitized animals. This study expands the knowledge on parasites of C. kuhlii and its vulnerability to parasites, contributing to constructing an epidemiological profile of environmental health.
Helmintos de Sagui-de-wied (Callithrix kuhlii (Coimbra-Filho, 1985) (Primates: Callitrichidae)) da Mata Atlântica, Sul da Bahia, Brasil
Keywords: alpha taxonomy; morphology; Neotropical Primates